An Ionic Liquid State Composed of Superoxide Radical Anions and Crownether-Coordinated Potassium Cations. Issue 8 (1st January 2017) - Kitada, Atsushi; Ishikawa, Daisuke; Fukami, Kazuhiro; Murase, Kuniaki
Abstract : We report an "ionic liquid state" substance composed of superoxide radical anions (O2 − ) and crownether-coordinated potassium cations. A binary mixture of 18-crown-6-ether (18C6) and potassium superoxide (KO2 ) becomes liquid above ca. 38°C. The coordination of 18C6 to K + and the presence of O2 − were confirmed in the liquid state by Raman spectroscopy measurements. Below 38°C, however, the 18C6-KO2 mixture does not form a complex but undergoes phase separation to parent phases of solid 18C6 and KO2, because the ion-dipole interaction between K + and 18C6 is overwhelmed by the ion-ion interaction between K + and O2 − . In other words, the pair of O2 − and 18C6-coordinated K + only appears above the melting point of pure 18C6, to form an "ionic liquid state". Among radical-containing ionic liquids, the liquid 18C6-KO2 mixture has high fluidity and comparable conductivity. The findings show stabilization of superoxide radical anions at liquid state with high concentration, which could be used for many radical reactions.